Nocebo Effects of Clinical Communication and Placebo Effects of Positive Suggestions on Respiratory Muscle Strength - Zech, Nina; Scharl, Leoni; Seemann, Milena; Pfeifer, Michael; Hansen, Ernil (Frontiers in Psychology, 2022)
Introduction: The effects of specific suggestions are usually studied by measuring parameters that are directly addressed by these suggestions. We recently proposed the use of a uniform, unrelated, and objective measure like maximal muscle strength that allows comparison of suggestions to avoid nocebo effects and thus to improve communication. Since reduced breathing strength might impair respiration and increase the risk of post-operative pulmonary complications, the aim of the present study was to evaluate the effects of the suggestions on respiratory muscle power. Both the identification and neutralization of negative suggestions in the clinical context and stimulating suggestions could improve breathing force, a predictor of physical fitness and convalescence. Methods In 50 healthy, adult volunteers, respiratory muscle strength was measured by maximal inspiratory and expiratory pressures, as well as by maximal inspiratory and expiratory flows. Baseline was compared to values after application of eleven suggestions, five out of clinical context, including memory of negative or positive past, risk information for informed consent, and a non-verbal suggestion. Six stimulating suggestions included self-affirmation, empowering words, a heroic mirror image, and an imagination. Results All suggestions showed an impact on respiratory muscle strength, indicating placebo and nocebo effects. No single parameter could represent the breathing force in its complexity, however, trends and different specific aspects of it were measured. The strongest reaction was observed with the recall of a previous negative situation resulting in a reduction in expiratory flow to 96.1% of baseline (p = 0.041). After risk information, a decrease was observed in three of the parameters, with the highest extend in expiratory pressure by 4.4%. This nocebo effect was neutralized by adding positive aspects to the risk information. Every intended strengthening suggestion resulted in statistically significant increases of at least one parameter, with changes of up to 10% (e.g., MEP 110.3%, p = 0.001), indicating placebo effects. Here, expiration was more affected than inspiration. Sex was the only influencing factor reaching statistical significance, with stronger reactions in women. Conclusion Respiratory muscle strength proved to be sensitive to suggestions with clinical context, as well as suggestions intended for stimulation. With this objective measurement, evaluation, and comparison of different suggestions is possible to help avoid nocebo effects. The demonstrated effect of supporting suggestions can be followed up and used in clinical practice.